Migration and Workforce Planning in Medicine with Special Focus on Anesthesiology - Mellin-Olsen, Jannicke (Frontiers in Medicine, 2017)
Counting health personnel and defining migration is more complicated than one should think at first glance. Migrating health workers are not a homogenous group, and many factors cause people to migrate - not only low wages, but also lack of professional development possibilities, poor job satisfaction, outdated equipment, unsafe environment and more. The opposite factors encourage people to stay. Many countries, including high income countries benefit from remittances from migrating individuals. The World Health Organization has installed a code of Practice on the international recruitment of health workers. Although member countries have committed to follow this Code, it is not widely adhered to. Planning for the future is difficult, also because there are so many unknown factors related to the development of health care levels, policies, inflow and outflow and more. Action must be taken in both donor and receiving countries. In anaesthesiology, there is a huge workforce deficit globally. The world would need 136,000 additional physician anaesthesia providers today in order to achieve an absolute minimum of five per 100,000 population. This will not happen unless all countries follow those that already have taken proactive steps in leading the direction forward. Anaesthesiology Society involvement is crucial.